Impact of endurance exercise on the heart of cyclists: A systematic review and meta-analysis - Wundersitz, D. W. T.; Gordon, B. A.; Lavie, C. J.; Nadurata, V.; Kingsley, M. I. C. (Progress in Cardiovascular Diseases, 2020)
Objective: To compare heart structure and function in endurance athletes relative to participants of other sports and non-athletic controls in units relative to body size. A secondary objective was to assess the association between endurance cycling and cardiac abnormalities. Patients and methods: Five electronic databases (CINAHL, Cochrane Library, Medline, Scopus, and SPORTdiscus) were searched from the earliest record to 14 December 2019 to identify studies investigating cardiovascular structure and function in cyclists. Of the 4865 unique articles identified, 70 met inclusion criteria and of these, 22 articles presented 10 cardiovascular parameters in units relative to body size for meta-analysis and five presented data relating to incidence of cardiac abnormalities. Qualitative analysis was performed on remaining data. The overall quality of evidence was assessed using GRADE. Odds ratios were calculated to compare the incidence of cardiac abnormality. Results: Heart structure was significantly larger in cyclists compared to non-athletic controls for left ventricular: mass; end-diastolic volume, interventricular septal diameter and internal diameter; posterior wall thickness, and end-systolic internal diameter. Compared to high static and high dynamic sports (e.g., kayaking and canoeing), low-to-moderate static and moderate-to-high dynamic sports (e.g., running and swimming) and moderate-to-high static and low-to-moderate dynamic sports (e.g., bodybuilding and wrestling), endurance cyclists end-diastolic left ventricular internal diameter was consistently larger (mean difference 1.2-3.2?mm/m2). Cardiac abnormalities were higher in cyclists compared to controls (odds ratio: 1.5, 95%CI 1.2-1.8), but the types of cardiac abnormalities in cyclists were not different to other athletes. Conclusion: Endurance cycling is associated with a larger heart relative to body size and an increased incidence of cardiac abnormalities relative to controls.